From tradition to innovation: Examining Ifugao’s local weave products as One Town One Product – Next generation - Malinao, Client William M. (Faculty of Social and Political Science, Universitas Airlangga, 2025)
The traditional weaving industry in Lagawe, Ifugao, Philippines, is a vital cultural and economic asset rooted in indigenous knowledge and craftsmanship. However, the sustainability of these enterprises in the modern market context remains a pressing concern. This study aims to determine the current condition of traditional weaving businesses in Lagawe, Ifugao, using the One Town One Product—Next Generation criteria. Owners of traditional weaving businesses that were purposively selected in Lagawe, Ifugao, were interviewed in 2023. Using thematic and inductive analysis, findings revealed that handwoven products are valued for their cultural authenticity, craftsmanship, and durability. Weavers from Kiangan and Hingyon provide quality materials, ensuring the integrity of the weave. Consumers appreciate the uniqueness, symbolism, and artisanal quality, which enhance personal identity and cultural pride. However, the sector faces challenges in branding, product innovation, and packaging. Traditional designs are mostly limited to garments, restricting broader market appeal, while non-traditional items like bags show minimal design evolution, reducing competitiveness. Packaging lacks labeling, including care instructions and cultural context, weakening branding and customer education. Quality control depends largely on raw materials and weaving techniques, but durability also relies on customer handling. Participants highlighted variability in longevity, suggesting the need for consumer education. Innovation that balances modernization with cultural preservation is essential for market sustainability. Overall, the traditional weaving industry in Ifugao showcases admirable product quality rooted in heritage. However, it must address gaps in market-oriented practices and product development to ensure long-term sustainability and relevance in a competitive and evolving global market.